Real-world global evidence of field hospitals during the COVID-19 pandemic / Siew King Ting ... [et.al.]. - Siew, King Ting; Tze, Wee Lai; Gabriel Puem, Lucy Batchy; Lau, Li Li; Dollery, Brian (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Disease pandemics have spawned the extensive use of field hospitals for disease outbreaks in modern history. The objective of this paper is to examine the characteristics, roles, and challenges facing field hospitals in battling the COVID-19 pandemic and to offer some policy recommendations for improving the performance of field hospitals. Using online academic databases, a literature review of COVID-19 field hospitals was conducted for six regions from 2020 - 2021: the Western Pacific, South East Asia, the Eastern Mediterranean, the Americas,Europe, and Africa.